2017
DOI: 10.18632/oncotarget.19384
|View full text |Cite
|
Sign up to set email alerts
|

1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol ameliorates arthritic joints through reducing neutrophil infiltration mediated by IL-6/STAT3 and MIP-2 activation

Abstract: The pathogenesis of rheumatoid arthritis (RA) has been implicated neutrophil extracellular traps (NETs) formation which could generate autoantigen. Neutrophil contributes to initiate and maintain the inflammatory process in the joint. In this study, we show that 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG) decreases neutrophil migration by regulating the activity of STAT3, a regulator of IL-6 and MIP-2 expression. PLAG caused a decrease in IL-6 production in the RAW264.7 macrophage cell line and in rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…As reported elsewhere, it has been shown that PLAG is an effective therapeutic candidate in different inflammatoryassociated diseases, such as rheumatoid arthritis, atopic dermatitis, asthma and hepatitis (20,(34)(35)(36). In addition, the therapeutic efficacy of PLAG has been demonstrated in chemotherapy and radiation-induced oral mucositis in hamster and mouse models, through the effective attenuation of neutrophil infiltration into cheek pouches and tongues and a decrease in inflammatory cytokines (37).…”
Section: Discussionmentioning
confidence: 73%
“…As reported elsewhere, it has been shown that PLAG is an effective therapeutic candidate in different inflammatoryassociated diseases, such as rheumatoid arthritis, atopic dermatitis, asthma and hepatitis (20,(34)(35)(36). In addition, the therapeutic efficacy of PLAG has been demonstrated in chemotherapy and radiation-induced oral mucositis in hamster and mouse models, through the effective attenuation of neutrophil infiltration into cheek pouches and tongues and a decrease in inflammatory cytokines (37).…”
Section: Discussionmentioning
confidence: 73%
“…The anti-metastasis effect of PLAG might be achieved by the disruption of PAR2 signaling, which mediates tumor cell activation in the presence of neutrophil elastase. PLAG has been studied in various inflammatory diseases including chemotherapy-induced neutropenia (CIN), chemo/radiation-induced oral mucositis (CRIOM), and rheumatoid arthritis (RA) [33][34][35]. Our results suggest that PLAG as a novel candidate molecule for the inhibition or retardation of tumor metastasis.…”
Section: Discussionmentioning
confidence: 86%
“…The 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG) is present in the antlers of the Sika deer and can be synthesized from glycerol, palmitic acid, and linoleic acid [32]. PLAG was recently shown to reduce the gemcitabine-induced neutropenia, oral mucositis and arthritis by modulating neutrophil movement [33][34][35]. There have not yet been any studies to determine if PLAG has the potential to control cancer progression by regulating neutrophil infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…It is chemically synthesized from glycerol, palmitic acid, and linoleic acid (28). PLAG reduces lipopolysaccharideinduced macrophage inflammatory protein 2 (MIP-2) and CXCL8 secretion (29). PLAG improves hepatic injury in concanavalin A-treated mice (9), and gemcitabine-induced neutropenia (30,31) and oral mucositis in hamster and mouse models (32), via modulation of neutrophil migration.…”
Section: Introductionmentioning
confidence: 99%